Cyborg HR: Knowledge intelligence solutions to support behavioral integration of senior management teams in the oil sector - Al-Musawi, Mohammed Raoof; Alsafo, Reyath Thea Azeez; Waham, Mohammed Ahmed (Journal of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study aims to examine the impact of Knowledge Intelligence (KI) on the behavioral integration of senior management teams within the oil sector, with a specific case study on the Misan Oil Company in Iraq. It explores how components of Knowledge Intelligence such as social capital and team creativity affect behavioral integration, including information sharing, collaborative decision-making, and diligence. Research methodology: A field survey was conducted involving 50 management team members from the Misan Oil Company. Quantitative data were analyzed using SPSS and Smart PLS software to examine the relationship between Knowledge Intelligence and behavioral integration. Results: The analysis showed a significant positive correlation between Knowledge Intelligence and behavioral integration (r = 0.307, p = 0.03). Among the dimensions, social capital recorded the highest mean (M = 3.90), while innovation participation scored the lowest (M = 2.98), indicating limited creativity engagement within teams. Conclusions: Knowledge Intelligence contributes meaningfully to improving behavioral integration among senior management, particularly through enhanced social capital. However, innovation-related involvement remains an area that requires strategic focus. Limitations: This study is limited to one company in Iraq's oil sector, which may restrict the generalizability of the findings to other industries or regions. Contribution: This study provides empirical evidence on how Knowledge Intelligence can be leveraged to strengthen integration and collaboration among top management in high-stakes industrial sectors.